Measuring and predicting maximal aerobic power in international-level intermittent sport athletes - Kilding, A. E.; Aziz, A. R.; Teh, K. C. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: The purpose of this study was to measure actual V.O2max during the multi-stage fitness test (MSFT) and to compare this with predicted values obtained using previously established, commonly used methods. We also wanted to determine a new and more accurate regression equation for the prediction of V.O2max in intermittent sport athletes. Methods.: Twenty-six, elite, male, intermittent sport athletes performed the MSFT with oxygen uptake (V.O2) and heart rate (HR) measured throughout. Paired t-tests were used to compare measured V.O2max with predicted V.O2max. Linear regression was used to determine the equation for the prediction of V.O2max from the total number of shuttles completed. Results: There were no differences between the two methods of predicting V.O2max, however, both predicted values (53.6±3.9 and 51.3±4 mL·kg-1·min-1) were significantly lower (9.3% and 13.2%, respectively) than measured V.O2max (59.1±6.6 mL·kg-1 ·min-1, P<0.001). Correlations between measured and predicted V.O2max were similar for both prediction methods (r=0.61, P=0.013 and r=0.68 and P=0.004). We present a new prediction equation [Y (V.O2max, mL·kg-1·min-1)=0.38 x total number of shuttles completed +25.98] (where R=0.69; R2=0.48; SEE=4.9 mL·kg-1·min-1; SEE%=8.3) which provides a more valid method of predicting actual max in intermittent sport athletes. Conclusions: A new regression equation to predict V.O2max in intermittent sport athletes has been established. Whilst some error in predicting V.O2max still exists, the new equation will provide coaches and sport-scientists with a more suitable equation with which to predict V.O2max in intermittent sport athletes.